2018
DOI: 10.6007/ijarbss/v8-i4/4127
|View full text |Cite
|
Sign up to set email alerts
|

A Case Study of Orang Asli Indigenous Knowledge in Traditional Medicine

Abstract: The practice of traditional healing is a continuous experience that has been part of national healthcare systems of Orang Asli (OA) societies for many years. Traditional medicine (TM) is part of OA Indigenous Knowledge (IK) and they use it from generation to generation for spirituality, health and longevity. However, these traditional medicinal specifically herbs and plants known to OA have become lessen due to the impact of deforestation, urbanization and modernization. In response to the issue, this case stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…In addition, this study is also essential to be documented as it has potential to expand and strengthen Orang Asli IKGT since this valuable and precious knowledge is in mortal danger and it is often forgotten or neglected due to modernization, deforestation, and glob-alization. This statement was supported by the study conducted by Lambin, Wahab, Choo, Mustapha, and Abdullah (2018a), which emphasized that is a need to document and preserve IK in medicinal plants for future prospective and generations before this knowledge weakened or vanishes.…”
Section: Introductionmentioning
confidence: 91%
See 2 more Smart Citations
“…In addition, this study is also essential to be documented as it has potential to expand and strengthen Orang Asli IKGT since this valuable and precious knowledge is in mortal danger and it is often forgotten or neglected due to modernization, deforestation, and glob-alization. This statement was supported by the study conducted by Lambin, Wahab, Choo, Mustapha, and Abdullah (2018a), which emphasized that is a need to document and preserve IK in medicinal plants for future prospective and generations before this knowledge weakened or vanishes.…”
Section: Introductionmentioning
confidence: 91%
“…3 which was reviewed in 1974, Orang Asli is deined as any of which the father is a member of the Orang Asli tribes, who speaks Orang Asli languages and follows the way of life, beliefs and traditions of Orang Asli's including the descent through the man (Jabatan Kemajuan Orang Asli Malaysia, 2017). There is a large number of published studies such as (Carey, 1976;Dentan, 1968;Lambin, Wahab, Choo, Mustapha, & Abdullah, 2018b;Ong & Azliza, 2015;Ong, Faezah, & Milow, 2012;Mustapha, Omar, Hassan, Yasin, & Salleh, 2010) which stated that Orang Asli can be divided into three ethnolinguistic groups, namely the Negrito (Semang), Senoi and Proto-Malay (Aboriginal Malay) with six different tribes in each main groups (Figure 1). These six different tribes which can be further sub-divided into 18 sub-tribes with their own physical characteristics, linguistic af inities, cultural practices (Ang et al, 2011;Bellwood, 1997;Hood, 2006;Nicholas, 1996) with unique features, lifestyles, and languages (Abdul Ghani Azmi, 2017).…”
Section: Literature Review Orang Aslimentioning
confidence: 99%
See 1 more Smart Citation
“…At the same time, such problems are commonly associated with several other factors, for example inconducive school environment including teaching and learning issues and also lack of motivation on the importance of education from the surrounding community (Lambin et al, 2018). This is parallel with the study by Rabahi, Yusof and Awang (2016) who found that the reasons for Orang Asli children to drop out from school are lack of interest in schooling, negative attitudes toward formal learning, having to live in poverty, lack of support from schools, lack of awareness amongst parents, inconducive school environment and sociocultural climate.…”
Section: Orang Asli Education Issues In Malaysiamentioning
confidence: 99%
“…Based on their geographical distribution, language, and morphological characteristics, Orang Asli are divided into three major tribes and 18 sub-tribes within the Negrito (Semang), Senoi and Proto-Malay (Aboriginal Malay) (Abdullah et al, 2016). However, they live in a heterogeneous setting because each sub-tribe has its own respective followed trait (Lambin, Wahab, Choo, Mustapha, & Abdullah, 2018).…”
Section: Orang Asli Community In Malaysiamentioning
confidence: 99%